2011
DOI: 10.1007/s11916-011-0231-1
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Excitability in Chronic Migraine

Abstract: A proportion of episodic migraine patients experiences a progressive increase in attack frequency leading to chronic migraine (CM). The most frequent external factor that leads to headache chronification is medication overuse. The neurobiological bases of headache chronification and of the vicious circle of medication overconsumption are not completely elucidated. More recently, the same neurophysiological methods used to study episodic migraine were applied to CM and medication-overuse headache (MOH). Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 49 publications
(61 reference statements)
2
79
1
2
Order By: Relevance
“…Interestingly, quantitative electromyography (EMG) recordings in 23 chronic migraine patients during eTNS with the Cefaly ® showed an increase of median frequency and amplitude of the myoelectrical signal in anterior temporalis, auricularis posterior, and middle trapezius muscles, but not in frontalis (37). The significance of this finding for the mode of action of the device is doubtful, the more so that it is unlikely that pericranial muscle activity plays a pathogenic role in chronic migraine (38).…”
Section: Peripheral Mechanismsmentioning
confidence: 98%
“…Interestingly, quantitative electromyography (EMG) recordings in 23 chronic migraine patients during eTNS with the Cefaly ® showed an increase of median frequency and amplitude of the myoelectrical signal in anterior temporalis, auricularis posterior, and middle trapezius muscles, but not in frontalis (37). The significance of this finding for the mode of action of the device is doubtful, the more so that it is unlikely that pericranial muscle activity plays a pathogenic role in chronic migraine (38).…”
Section: Peripheral Mechanismsmentioning
confidence: 98%
“…Interestingly, all these mechanisms might be involved in the process of headache chronification. In particular, enhanced activation of the central glutaminergic system might be responsible of an increased cortical excitability [25]; in addiction, repeated morphine administration has also been shown to increase levels of pro-nociceptive peptides, as calcitonin generelated peptide (CGRP) and substance P, within the dorsal root ganglia in animal studies [26,27]. Enhanced levels of CGRP and substance P might be present in dural afferents of trigeminal ganglia in migraine patients assuming opioids.…”
mentioning
confidence: 99%
“…PD power was also significantly superior in episodic migraine as compared to chronic migraine. This could be related to the changes in visual cortex responsiveness over the migraine cycle [20,22] and between episodic and chronic migraine [23]. For instance, during stimulus repetition, EEG and magnetoencephalographic visual evoked responses lack habituation in episodic migraine between attacks, but habituate normally during attacks and in chronic migraine [24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, during stimulus repetition, EEG and magnetoencephalographic visual evoked responses lack habituation in episodic migraine between attacks, but habituate normally during attacks and in chronic migraine [24,25,26]. Since the response pattern in chronic migraine is indistinguishable from that found during attacks in episodic migraine, it was suggested that chronic migraine patients are locked in an "ictal-like state" [23,27]. Patients with a high attack frequency are at greater risk of being recorded close to an attack than those with a low number of monthly attacks.…”
Section: Discussionmentioning
confidence: 99%